First steps in the implementation of a COAP and Block-chain server for green hydrogen certification - Jaimes Soria, Leandro (2024)
In the face of rising concerns about climate change, the energy sector is undergoing a digital transformation. IoT and Blockchain technology has emerged as a promising solution to ensure security, traceability, and efficiency in energy management, particularly in certifying the origin of energy. Various projects in the energy sector are discussed, highlighting how these initiatives are transforming the way energy is produced, distributed, and consumed. The paper focuses on the work done to implement a central node for handling received hydrogen gas flow measurements using the COAP protocol and the initial steps in the implementation of a blockchain node.